A Randomized Clinical Trial to Evaluate the Efficacy of an Oral Probiotic in Acne Vulgaris - Cristina Eguren; Ariadna Navarro-Blasco; Marina Corral-Forteza; Alejandra Reolid-Pérez; Núria Setó-Torrent; Alejandro García-Navarro; David Prieto-Merino; Eva Núñez-Delegido; Pedro Sánchez-Pellicer; Vicente Navarro-López (Medical Journals Sweden, 2024)
The relevance of the gut microbiota in some skin inflammatory diseases, including acne vulgaris, has been emphasized. Probiotics could play a role in the modulation of the microbiota, improving the clinical course of this disease. A 12-week randomized, double-blind, placebo-controlled, clinical trial with patients aged 12 to 30 years with acne vulgaris was conducted. The study product was a capsule composed of the probiotic Lacticaseibacillus rhamnosus (CECT 30031) and the cyanobacterium Arthrospira platensis (BEA_IDA_0074B). Patients with improvement in the Acne Global Severity Scale were 10/34 (29.41%) in the placebo group compared with 20/40 (50%) in the probiotic group (p = 0.03). A significant reduction (p = 0.03) in the number of non-inflammatory acne lesions was observed in the probiotic group (-18.60 [-24.38 to -12.82]) vs the placebo group (-10.54 [-17.43 to -3.66]). Regarding the number of total  lesions, a reduction almost reaching statistical significance (p = 0.06) was observed in the probiotic group (-27.94 [-36.35 to -19.53]) compared with the placebo group (-18.31 [-28.21 to -8.41]). In addition, patients with improvement attending the Global Acne Grading System were 7/34 (20.58%) in the placebo group vs 17/40 (42.50%) in the probiotic group (p = 0.02). The number of adverse events was similar in both groups. The probiotic used in this study was effective and well tolerated, and it should be considered for acne vulgaris patients.